Danish flexicurity: Rights and duties - Claus Thustrup Kreiner; Michael Svarer (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
Denmark is one of the richest countries in the world and achieves this in combination with low inequality, low unemployment, and high income security. This performance is often attributed to the Danish labor market model characterized by what has become known as flexicurity. This essay describes and evaluates Danish flexicurity. The Danish experience shows that flexicurity in itself, i.e., flexible hiring and firing rules for firms combined with high income security for workers, is insufficient for successful outcomes. The flexicurity policy also needs to include comprehensive active labor market programs (ALMPs) with compulsory participation for recipients of unemployment compensation. Denmark spends more on active labor market programs than any other OECD country. We review theory showing how ALMPs can mitigate adverse selection and moral hazard problems associated with high income security and review empirical evidence on the effectiveness of ALMPs from the ongoing Danish policy evaluation, which includes a systematic use of randomized experiments. We also discuss the aptness of flexicurity to meet challenges from globalization, automation, and immigration and the trade-offs that the United States (or other countries) would face in adopting a flexicurity policy.
Keywords: 330